Global maize production, consumption and trade: trends and R&D implications - Erenstein, Olaf; Debello, Moti J.; Sonder, Kai; Mottaleb, Khondoker A.; Prasanna, Boddupalli M. (Springer, 2022)
Since its domestication some 9,000 years ago, maize (Zea mays L.; corn) has played an increasing and diverse role in global agri-food systems. Global maize production has surged in the past few decades, propelled by rising demand and a combination of technological advances, yield increases and area expansion. Maize is already the leading cereal in terms of production volume and is set to become the most widely grown and traded crop in the coming decade. It is a versatile multi-purpose crop, primarily used as a feed globally, but also is important as a food crop, especially in sub-Saharan Africa and Latin America, besides other non-food uses. This paper reviews maize production, consumption, and international trade to examine the changing trends in global supply and demand conditions over the past quarter century and the implications for research and development (R&D), particularly in the Global South. The inclusiveness and sustainability of the ongoing transformation of agri-food systems in the Global South merit particular attention. There is a need for further investments in R&D, particularly to enhance maize’s food and livelihood security roles and to sustainably intensify maize production while staying within the planetary boundaries.